Good News! Communication Findings May be Underestimated: Comparing Effect Sizes with Self-Reported and Logged Smartphone Use Data. Issue 5 (24th August 2020) - Jones-Jang, S Mo; Heo, Yu-Jin; McKeever, Robert; Kim, Jung-Hyun; Moscowitz, Leigh; Moscowitz, David
Abstract: Despite long-standing concerns over self-reported measures of media use, media research has relied heavily on self-reported data. This study not only examined discrepancies between survey and logged smartphone data but assessed whether correlational outcomes using self-reported measures produce greater or smaller effect sizes compared to outcomes using logged measures. College students (n = 294) and MTurk workers (n = 291) provided self-reported and logged data of smartphone use over seven days. The correlations we examined involved four psychosocial contexts, including bridging, bonding, well-being, and problematic use of smartphones. The results showed that the effect sizes of correlations using self-reported data tend to be smaller compared to those using logged data. We believe that this is a hopeful message to the field. This could mean that extant survey results have not erroneously inflated communication findings and that communication researchers still have a lot to reveal with further refined measures.